TOTAL QUALITY MANAGEMENT IN MECHANICAL INDUSTRY - Sibete Godfrey Ayeabu; Waratimi Emomotimi Obonika; Worgu Fortune Osaruchi (International Journal of Innovations in Engineering Research and Technology, 2023)
Total Quality Management is a management idea and organization,s operations aimed at harnessing human and material resources of the firm in the best effective way to actualize the goals of the company. It enlightened the origin and content of TQM approaches to TQM, areas /elements of Total Quality Management. The paper also encapsulates the importance of TQM in the Mechanical Industry. Thus, it is concluded that TQM includes ten core values and ideas critical to formulate organization’s vision of quality top management support, planning and organizing of the effort and careful accomplishment and regulation of the process. The researchers therefore recommended that the primary focus of all TQM strategy satisfy the customer’s needs at least and match their expectations as well as continuous improvement, quick response, public responsibility etc.